Algorithms - Sedgewick, Robert; Wayne, Kevin (Upper Saddle River, New Jersey : Addision-Wesley Publishing Company, 2011)
This fourth edition of Robert Sedgewick and Kevin Wayne$1 (Bs Algorithms is the leading textbook on algorithms today and is widely used in colleges and universities worldwide. This book surveys the most important computer algorithms currently in use and provides a full treatment of data structures and algorithms for sorting, searching, graph processing, and string processing--including fifty algorithms every programmer should know. In this edition, new Java implementations are written in an accessible modular programming style, where all of the code is exposed to the reader and ready to use.s
Chapter 1: Fundamentals 1.1 Programming Model 1.2 Data Abstraction 1.3 Queues, Stacks, and Bags 1.4 Analysis of Algorithms 1.5 Case Study: Union-Find Chapter 2: Sorting 2.1 Elementary Sorts 2.1 Elementary Sorts 2.2 Mergesort 2.3 Quicksort 2.4 Priority Queues 2.5 Applications Chapter 3: Searching 3.1 Symbol Tables 3.1 Symbol Tables 3.2 Binary Search Trees 3.3 Balanced Search Trees 3.4 Hash Tables 3.5 Applications Chapter 4: Graphs 4.1 Undirected graphs 4.1 Undirected graphs 4.2 Directed graphs 4.3 Minimum Spanning Trees 4.4 Shortest Paths Chapter 5: Strings 5.1 String Sorts 5.1 String Sorts 5.2 Tries 5.3 Substring Search 5.4 Regular Expressions 5.5 Data Compression Context Systems Programming Systems Programming Scientific Computing Commercial Applications Operations Research Intractability Index
Includes bibliographical references and index.
Keywords: COMPUTER ALGORITHMS -- TEXTBOOKS